Resepsi Pembaca pada Situs Daring terhadap Novel Ningen Shikkaku Karya Dazai Osamu - Haliza, Nur; El Risman, Yunita (NAWA: Journal of Japanese Studies, 2025)
This article examines online reader reception of Dazai Osamu’s novel Ningen Shikkaku using Hans Robert Jauss’s literary reception theory. The study focuses on readers’ responses to the novel’s intrinsic elements such as theme, character, plot, setting, and language style as reflected in reviews posted on Amazon, Goodreads, and LibraryThing. This qualitative research employs content analysis and data interpretation based on Jauss’s concepts of horizon of expectations, aesthetic distance, historical reception, and aesthetic experience. The findings reveal that readers respond to Yozo’s narrative affectively and reflectively, interpreting it both as a portrayal of individual alienation in postwar Japanese society and as an expression of existential struggle that transcends cultural boundaries. The novel’s fragmented plot, brutally honest yet poetic language, and historical Japanese setting emerge as key elements shaping reader perception. This study affirms that literary reception is not determined solely by the text, but also by the interaction between the act of reading, cultural background, and the aesthetic expectations of contemporary readers. As such, the research contributes to the broader discourse on modern Japanese literature from the perspective of global readership.